IBM FlashSystem and VMware implementation and best practices guide - Gucer, Vasfi; Bolland, Duane; Boyacioglu, Nezih; Fincher, Jordan; Green, David; Hawkins, Warren; Rufai, Ibrahim Alade; Torolho, Leandro (IBM Redbooks, 2022)
This IBM® Redbooks® publication details the configuration and best practices for using the IBM FlashSystem® family of storage products within a VMware environment. The first version of this book was published in 2021 and specifically addressed IBM Spectrum® Virtualize Version 8.4 with VMware vSphere 7.0. This second version of this book includes all the enhancements that are available with IBM Spectrum Virtualize 8.5. This book is intended for presales consulting engineers, sales engineers, and IBM clients who want to deploy IBM FlashSystem storage systems in virtualized data centers that are based on VMware vSphere.
Includes bibliographical references
Keywords: Computer storage devices; Information storage and retrieval systems; Database management; Information technology -- Management; Ordinateurs; Mémoires; Systèmes d'information; Bases de données; Gestion; Technologie de l'information; Gestion; Information technology; Management